Landscape diversity in North Macedonia - Melovski, Ljupčo; Jovanovska, Daniela; Hristovski, Slavčo (Macedonian Journal of Ecology and Environment, 2019)
This study provides data on landscape diversity in North Macedonia. Total of 41 landscape types have been identified, on a higher hierarchical level organised within 8 landscape groups. The character of natural landscapes is provided by relief, climate, geology, soils and vegetation cover set along elevation gradient. The character of cultural landscapes is withal provided by land use and settlement patterns with reference to landscape cultural specifics and historicity. Research outputs provide an opportunity to further address the importance of spatial configuration for ecological processes and hopes to serve as a methodological and conceptual guideline for succeeding national landscape classifications in the region.